Perundungan di Sekolah sebagai Indikator Kegagalan Internalisasi Etika Sosial: Implikasinya terhadap Kualitas Sumber Daya Manusia - Suwandi; Kurnia, Heri (CV. Kurnia Grup, 2025)
Bullying in schools is an educational issue that has a serious impact on character building, mental health, and the quality of human resources. This phenomenon shows that schools have not been fully successful in carrying out their function as a space for the internalization of social ethics and human values. This article aims to analyze the forms and dynamics of bullying in schools, understand bullying as an indicator of the failure of social ethics internalization, and examine its implications for the quality of human resources. This study uses the systematic literature review (SLR) method with a PRISMA approach to relevant national and international scientific articles published in the last five years. The results show that bullying occurs in various forms, including verbal, relational, and digital, which are influenced by power relations, school culture, and weak character education. Bullying also reflects a low respect for human dignity and social justice values in educational practices. These findings confirm that bullying has long-term implications for the quality of human resources through disruptions to the character, social competence, and mental health of students. Therefore, strengthening character education and social ethics in an integrated manner is an important strategy in preventing bullying and developing sustainable human resources.